Atlas of the European Reformations - Dowley, Tim; Rowland, Nicholas (Minneapolis. : Fortress Press., 2015)
A new atlas of the European Reformations has been keenly needed. Fortress Press is pleased to offer the Atlas of the European Reformations. The atlas is built new from the ground up. Featuring more than sixty brand new maps, graphics, and timelines, the atlas is a necessary companion to any study of the Reformation era. Concise, helpful text written by acknowledged authorities guides the experience and interprets the visuals. Consciously written for students at any level, the volume is prefect for independent or classroom use. -- from back cover
Timeline AD 1300-1700 --Before the Reformation.The rise of learning ;The Waldensians ;The devotio modern ; The Great Schism ;Wyclif and the Lollards ;Jan Hus and the Hussites ;The rise of printing ;The Italian Renaissance ; The Northern Renaissance ;The Catholic Church in 1500 ;Portuguese voyages of discovery ;Spain explores the West ; The world circumnavigated --Reformation.Charles V ;Martin Luther ;The German Knights' War ;The Peasants' War ; The radical Reformation ;Jewish oppression ;Philipp Melanchthon ;Protestantism in 1530 Lutheranism consolidates ;Huldrych Zwingli
Includes bibliographical references (pages 148-149), gazetteer, and index
Keywords: Ecclesiastical geography -- Europe -- Maps; Reformation -- Maps; Church history -- Middle Ages, 600-1500; Church history -- 16th century; Church history -- 17th century; Atlases; Maps; Atlases